2020
DOI: 10.2147/cmar.s249738
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeted Inhibition of CCL22 by miR-130a-5p Can Enhance the Sensitivity of Cisplatin-Resistant Gastric Cancer Cells to Chemotherapy</p>

Abstract: This study set out to explore the regulatory mechanism of miR-130a-5p in cisplatin (DDP)-resistant gastric cancer (GC) cells. Materials and Methods: Forty cases of GC and paracancerous tissues were collected, and the miR-130a-5p and CCL22 levels were detected by qRT-PCR. DDP-resistant cell lines of GC cells were established. Cell viability, invasion, and apoptosis were measured by CCK-8, Transwell, and flow cytometry, respectively. The relationship between miR-130a-5p and CCL22 was verified by dual-luciferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, miRNA-155 has been acknowledged in cancer drug resistance and as a target for miRNA-based therapy. Several reports have demonstrated that miRNA-130a-5p is aberrantly expressed in various cancers, including lung cancer [ 8 ], gastric carcinoma [ 9 ], and renal carcinoma [ 10 ]. Besides, miRNA-130a-5p can also regulate chemosensitivity, proliferation, and metastasis in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNA-155 has been acknowledged in cancer drug resistance and as a target for miRNA-based therapy. Several reports have demonstrated that miRNA-130a-5p is aberrantly expressed in various cancers, including lung cancer [ 8 ], gastric carcinoma [ 9 ], and renal carcinoma [ 10 ]. Besides, miRNA-130a-5p can also regulate chemosensitivity, proliferation, and metastasis in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-130a-5p was reported to inhibit tumor invasion and metastatic potential in non-small cell lung cancer [36]. MiR-130a-5p enhanced the sensitivity of cisplatin-resistant gastric cancer cells to chemotherapy [37]. PKP4 was also called "p0071", which were reported to interact with Ecadherin to promote the invasion and metastasis of cancer cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that solasonine inhibits GC cell proliferation and improves its chemosensitivity to paclitaxel by up-regulating miR-486-5p ( 41 ). In addition, Fang et al indicated that overexpressing miR-130a-5p reduces the malignant proliferation and invasion of GC cells, promotes apoptosis, and strengthens the chemosensitivity of GC to CDDP by targeting CCL22 ( 42 ). Also, miRNAs mediate EMT in GC.…”
Section: Discussionmentioning
confidence: 99%